An Overview of the Beneficial and Detrimental Consequences of Codes of Ethics in A Practical Environment - Zanyar Nathir Ghafar (Mutiara: Multidiciplinary Scientifict Journal, 2024)
The piece of writing aims to contemplate the possibility of a scenario where codes of ethics are unnecessary or unsuitably used. The potential benefits of codes of ethics are well recognized, and there is much research available on this topic. There is a significant amount of literature available on the factors that influence the acceptance of ethical norms. There is a much less number of publications discussing the ineffectiveness of ethical norms within a specific framework of reality. Insufficient attention is given to the adverse effects that arise from the incomplete use of codes of ethics. The study findings demonstrate the circumstances in which a code of ethics may be ineffective and lacking in actual impact. The study highlights how certain components of a code of ethics might result in harmful outcomes when they are embraced and put into practice.